Analysis of Islamic Educational Values in the Book Puncak Ilmu Adalah Akhlak - Nur Havidah; Nanang Abdillah; Muhammad Arifudin (Kuttab: Jurnal Ilmu Pendidikan Islam, 2026)
Moral degradation among young generations has become a serious issue that requires strengthening character education based on Islamic values. Islamic Religious Education plays a strategic role in shaping students who are not only intellectually competent but also morally and spiritually grounded. This study aims to identify and analyze the values of Islamic Religious Education contained in the book Puncak Ilmu Adalah Akhlak by Mhd. Rois Almaududy and to explain their relevance to strengthening Islamic character education. This research employed a qualitative approach using library research and content analysis methods. The findings reveal that the book integrates Islamic educational values across three main dimensions: akidah, akhlak, and sharia. The integration of these dimensions emphasizes that moral character represents the culmination of knowledge. These findings are relevant as both a conceptual and practical foundation for strengthening students’ Islamic character education amid moral crises and the challenges of globalization.